Bilinear multipliers and transference - Oscar Blasco (International Journal of Mathematics and Mathematical Sciences)
We give de Leeuw-type transference theorems for bilinear multipliers. In particular, it is shown that bilinear multipliers arising from regulated functions m(ξ,η) in ℝ×ℝ can be transferred to bilinear multipliers acting on 𝕋×𝕋 and ℤ×ℤ. The results follow from the description of bilinear multipliers on the discrete real line acting on Lp-spaces.